Keystones in a Tangled Bank: Ecological network studies highlight the importance of individual species to community conservation - Lewinsohn, Thomas (2012)
In the past decade, ecologists have increasingly applied complex network theory (1, 2) to ecological interactions, both in entire food webs (3) and in networks representing ecological interactions, especially those between plants and their animal pollinators or seed dispersers (4). How important are individual species to the maintenance of such ecological networks? On page 1489 of this issue, Stouffer et al. (5) analyze terrestrial, freshwater, and marine food webs to infer the contributions of individual species to network stability. In a related field study on page 1486 of this issue, Aizen et al. (6) explore plant and pollinator webs on a landscape scale. Using a different field study design, Pocock et al. (7) recently focused on a local community in which several webs of different kinds of interactions and organisms form a composite network.